1.
1)
[tex] {(c - 6)}^{2} = {c}^{2} - 12c + 36[/tex]
2)
[tex] {(2a - 3b)}^{2} = {4a}^{2} - 12ab + {9b}^{2} [/tex]
3)
[tex](5 - a)(5 + a) = 25 - {a}^{2} [/tex]
4)
[tex](7x + 10y)(10y - 7x) = {100y}^{2} - {49x}^{2} [/tex]
2.
[tex] {b}^{2} - 49 = (b - 7)(b + 7)[/tex]
[tex] {c}^{2} - 8c + 16 = {(c - 4)}^{2} [/tex]
[tex]100 - 9 {x}^{2} = (10 - 3x)(10 + 3x)[/tex]
[tex] {4a}^{2} + 20ab + 25b {}^{2} = {(2a + 5b)}^{2} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1.
1)
[tex] {(c - 6)}^{2} = {c}^{2} - 12c + 36[/tex]
2)
[tex] {(2a - 3b)}^{2} = {4a}^{2} - 12ab + {9b}^{2} [/tex]
3)
[tex](5 - a)(5 + a) = 25 - {a}^{2} [/tex]
4)
[tex](7x + 10y)(10y - 7x) = {100y}^{2} - {49x}^{2} [/tex]
2.
1)
[tex] {b}^{2} - 49 = (b - 7)(b + 7)[/tex]
2)
[tex] {c}^{2} - 8c + 16 = {(c - 4)}^{2} [/tex]
3)
[tex]100 - 9 {x}^{2} = (10 - 3x)(10 + 3x)[/tex]
4)
[tex] {4a}^{2} + 20ab + 25b {}^{2} = {(2a + 5b)}^{2} [/tex]